A Field Study on the Relationship between Personality and Professional Commitment - Ucar, Omur; Ersoy, Asli; Aksu, Akin; Ehtiyar, V Ruya (International Journal of Business Strategy and Social Sciences, 2020)
The study aims to reveal the relationship between the personality traits and professional commitment of university students and to determine whether personality affects professional commitment. For this purpose, 272 students studying at Akdeniz University, Faculty of Tourism participated in the research. A questionnaire was used as the data collection tool. Arithmetic mean and standard deviation values were calculated to determine students’ personality traits and organizational commitment levels. Correlation analysis was performed to calculate the relationships between the variables discussed in the study, and multiple linear regression analysis was carried out to identify the predictive power that the independent variables had on the dependent variables. Research results indicated that there was a significant and positive relationship between the students' personality traits and professional commitment levels. In addition, it was determined that the extraversion personality trait was a significant predictor of the affective commitment dimension, neuroticism personality trait was a significant predictor of the continuance commitment dimension, and agreeableness personality trait was a significant predictor of the normative commitment dimension. It is believed that the results of the study will provide concrete information about the relationship between professional commitment, one of the main problem areas of the sector, and personality, one of the key concerns and interesting topics in the field of organizational behavior and bring considerable benefits to the business world.